1988
DOI: 10.1177/156482658801000419
|View full text |Cite
|
Sign up to set email alerts
|

Selected Socio-economic, Environmental, Maternal, and Child Factors Associated with the Nutritional Status of Infants and Toddlers

Abstract: Malnutrition is one of the most widespread public health problems facing India today. Among the highly susceptible groups are infants and toddlers (0-3 years old), who constitute nearly 10% of Indian's population. Unfortunately, they are largely ignored from a nutritional standpoint [1]. There is now a growing realization that malnutrition is not only a problem of food supply but can also be a function of more complex big-social and behavioural determinants affecting child feeding and rearing [2]. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…Several studies have shown that the nutrition status of the children of mothers working outside the home is poorer than that of children of non-working women [1][2][3]. Such findings could be due either to the quality of the alternative child care or to a relationship between poverty and the consequent necessity of working outside the home.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the nutrition status of the children of mothers working outside the home is poorer than that of children of non-working women [1][2][3]. Such findings could be due either to the quality of the alternative child care or to a relationship between poverty and the consequent necessity of working outside the home.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of these factors is particularly important in planning out preventive strategies to decrease the burden of undernutrition. Several previous studies have shown that a number of perinatal factors, including birth weight, birth interval, parity, gestational age 4-6 , and the child's gender 7 , are related to the nutritional status in children. Furthermore, socio-economic conditions 4,8 , living standards, water and sanitation, food intake, weaning practices, and maternal education 4,9 , are also shown to affect the nutritional status in young children.…”
Section: Introductionmentioning
confidence: 99%
“…Breast milk provides the nutrients and antibodies necessary to sustain infant growth and development, but lactating mothers cannot provide adequate amounts of milk if they themselves are malnourished as a result of chronic poverty, often combined with seasonal fluctuations in food availability (Gopaldas et al 1988;Teokul et al 1986). Early studies in Haiti have found prolonged breastfeeding common in the rural areas, and less widely endorsed in urban areas.…”
Section: Inf Ant Feeding and Weaningmentioning
confidence: 99%
“…Environmental factors play an important role in affecting the health status of individuals. Conditions in the surrounding environment, primarily water sources and sewage and waste dumping grounds, often provide growth mediums for animal and bacterial borne diseases (Gopaldas et al 1988;Henry 1981;Isely 1984).…”
Section: Environmental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation